2015
DOI: 10.1007/s00436-015-4499-7
|View full text |Cite
|
Sign up to set email alerts
|

Case of human Dirofilaria repens infection manifested by cutaneous larva migrans syndrome

Abstract: Dirofilaria repens, parasite of subcutaneous tissues of dogs and other carnivores, represents high infection risk for animals and humans in Europe. In men, infection usually presents as nodule in subcutaneous tissues or, less often, the lesions are localised around the eyes. The work presents first confirmed clinical case of human D. repens infection connected with cutaneous larva migrans syndrome. In patient, the migration of the worm caused true signs of creeping eruption, elevated sinuous track under the sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…Dirofilarial infections are relatively often accompanied with the parasite subcutaneous migration, and even cutaneous larva migrans syndrome was recorded in Slovak patient recently (6). Herein we present a rare and remarkable case of ocular dirofilariasis manifested by foregoing subcutaneous migration accompanied by severe headache symptoms.…”
Section: Dirofilariasis; Dirofilaria Repens;mentioning
confidence: 87%
See 1 more Smart Citation
“…Dirofilarial infections are relatively often accompanied with the parasite subcutaneous migration, and even cutaneous larva migrans syndrome was recorded in Slovak patient recently (6). Herein we present a rare and remarkable case of ocular dirofilariasis manifested by foregoing subcutaneous migration accompanied by severe headache symptoms.…”
Section: Dirofilariasis; Dirofilaria Repens;mentioning
confidence: 87%
“…The helminths occur in the form of a cystic lesion or are directly visible (3,11), with one, exceptionally two individuals detected (12). Despite of ocular dirofilariasis represents still less common form of the infection in comparison with subcutaneous form, during the last two decades progressive increase of its incidence has been reported in various European countries including Serbia, Greece, Belgium or Denmark (6,11,13,14).…”
Section: Discussionmentioning
confidence: 99%
“…A study of 74 cases of creeping dermatitis in Paris mainly found hookworm-related cutaneous larva migrans (HrCLM), very few cases of gnathostomiasis, loiasis, and cutaneous pili migrans, whereas there were no cases of dirofilariasis [20]. In Europe, three cases of human dirofilariasis have been reported in the literature with a creeping dermatitis episode: one in France with facial lesions [8], another in Italy with abdominal lesions [9], and the last one in Slovakia with cervical lesions [1]. All the cases developed in a subcutaneous nodule.…”
Section: Discussionmentioning
confidence: 99%
“…Only one report of circulating microfilaria in a human exists in medical literature [7] and a case report showing the present of microfilaria in a nodule examinated by fine needle aspiration [8].…”
Section: Discussionmentioning
confidence: 99%